Röntgenfluoreszenzgestützte Analyse der zwei bronzezeitlichen Hortinventare von Schellhorn und Fahrdorf (Schleswig-Holstein). - Finkeldey, Ilian (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
As part of my master's thesis from 2023/2024 »Traces of craftsmanship in metal – X-ray fluorescence-based analysis of the two Bronze Age hoard inventories from Schellhorn and Fahrdorf (Schleswig-Holstein)«, bronze objects from the two hoards discovered in Schleswig-Holstein, Schellhorn (1902) and Fahrdorf ( 2021), were examined using non-destructive X-ray fluorescence analysis (RF/XRF) and microscopy. Both hoards date to Period II of the Nordic Bronze Age and were selected for analysis due to their good state of preservation and typical artifact composition. The proposed presentation will discuss the generated measurement data in the light of the manufacturing processes, the corrosion processes, as well as in relation to conservation measures and thus contribute to the process analysis of XRF - data. Portable X-ray fluorescence (p-XRF) allows the composition of solid objects to be analysed quickly and easily, but the results are influenced by the state of preservation due to the low measuring depth, especially in the case of non-destructive analyses (which were a requirement by the State Museum for all artifacts). However, both hoard inventories processed showed specific anomalies on the surface that do not match the expected compositions of prehistoric artifacts. In consultation with the responsible conservator, the influence on the more recent finds could be attributed to the desalination method used. As in the case of the older finds from Schellhorn there is no documentation of any conservation measures that could help to explain the identification of the chemical anomaly. Several possibilities had to be considered, in particular natural and artificial corrosion processes. Ultimately, all anomalies could be classified as the traces of various restoration measures and thus compensated for in the processed data. The trace elements present in the adjusted data correspond to the composition typical for this period and region. Apart from the corrosion-related changes, the compositions of the objects are so similar, with one exception, that a connection between the two hoards could be assumed through a common origin of the raw materials, or perhaps even a common production site.